Identification and Quantification of the Component Composition of the Active Substance Gentamicin Sulfate by 1Н and 13С NMR Spectroscopy - S. V. Moiseev; N. E. Kuz’mina; E. Yu. Severinova; E. P. Simonova; V. V. Kosenko (Регуляторные исследования и экспертиза лекарственных средств)
Gentamicin sulfate is a broad-spectrum bactericidal aminoglycoside antibiotic produced by Micromonospora purpurea and used in clinical practice as an active substance containing a mixture of gentamicins C1 and C2. Gentamicin content is a standardised parameter controlled as part of a pharmaceutical product review. Currently, the quality control of the active substance gentamicin sulfate involves the use of high-performance liquid chromatography (HPLC) for the indirect identification of the component composition by comparison with a reference standard and for its quantification by calibration against the reference standard.The aim of the study was to develop a procedure for identifying and quantifying the components of the active substance gentamicin sulfate using nuclear magnetic resonance (NMR) spectroscopy that would not require reference standards.Materials and methods. The authors studied a sample of the active substance gentamicin sulfate using an Agilent DD2 NMR spectrometer operating at 600 MHz to record NMR spectra and an Agilent 1200 HPLC system equipped with a multiple wavelength detector (MWD) to obtain chromatograms.Results. Having determined the spectral properties of the C1, C1A, C2, C2A and C2B gentamicins comprising the active substance, the authors observed characteristic signals of the same type that corresponded to each of the gentamicins and did not overlap with other signals in the 1H and 13C spectra. These characteristic signals provided spectral markers indicative of the gentamicins of interest in the sample, with normalised integrated intensities equal to the mole fractions of the analytes. The authors compared NMR and HPLC measurements of the active substance composition.Conclusions. The authors developed a procedure for identifying and quantifying the constituents of the active substance gentamicin sulfate by 1H and 13C NMR spectroscopy, which requires less effort than HPLC procedures and no reference standards for the intended applications.